Dosimetric benefit of adaptive radiotherapy in the neoadjuvant management of canine and feline thymoma—An exploratory case series. (8th January 2018) - Rohrer Bley, C.; Meier, V.; Schneider, U.
Abstract : While surgery is the treatment of choice for thymomas, complete excision is not possible in a significant proportion of cases. For these patients, radiotherapy can be used as neoadjunctive, post‐operative adjunctive or sole therapy. During radiotherapy, rapid biological clearance of tumour cells is often observed, requiring adaptation of the treatment plan. Adaptive radiation therapy (RT) is a dynamic process, whereby the treatment plan is altered throughout the treatment course due to changes in morphologic, functional or positioning changes. With the hypothesis, that individually adapted replanning will massively reduce the dose to organs at risk (OAR) in a fast‐changing environment such as a rapidly responding thymoma, the dosimetric impact of adaptive treatment planning in 5 patients with large thymoma was measured. In all patients rapid tumour‐shrinkage of the gross tumour volume was observed after 1 week of therapy, with a mean shrinkage of 31.0% ± 15.2%, or a tumour regression of 5.2% per day. In consequence, there was a considerable change in position of organs such as heart and lung, both of them moving cranially into the high dose area upon tumour regression. After mid‐therapy replanning, the dose to OAR was significantly reduced, with −18.2% in the mean heart dose and −27.9% in the V20 lung dose. Adaptive planning led to a significantly reduced radiation dose and hence protection of OAR for these patients. It can be concluded that adaptive replanning should be considered for canine and feline thymoma patients receiving fractionated RT.